2012
DOI: 10.1007/s11746-012-2177-9
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐Enzymatic Synthesis and Antimicrobial Evaluation of Alkyloxy Propanol Amine‐Based Cationic Ether Lipids

Abstract: The present study involved the synthesis and antimicrobial evaluation of alkyloxy propanol amine‐based cationic lipids N,N‐dimethyl‐1‐octadecylamino‐3‐alkyloxy‐2‐propanol (series A, 7a–e) and N‐methyl‐N,N‐di‐(2‐hydroxy‐3‐alkyloxy‐2 propyl) octadecylamine (series B, 9a–e) and their acetylated derivatives (8a–e and 10a–e). A simple three‐step chemo‐enzymatic approach was employed for the synthesis of 7a–e and 9a–e in 71–80 and 67–88 % yields, respectively. The first step involved the synthesis of a series of gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Considerable research has been carried out on 2 H ‐1,4‐benzoxazin‐3(4 H )‐one in the medical field, while related pesticides have exhibited antifungal, [10,11] antibacterial, [12–14] herbicidal, [15,16] anticancer, [17,18] antitumor, [19] antileukaemia, [20] antagonist, [21] antioxidant, [22] and platelet aggregation inhibitor activities [23] ( Figure 1). Moreover, many reports demonstrate that compounds containing propanolamine moiety have wide‐ranging biological activities, including antifungal, [24] antibacterial, [25,26] anti‐HIV, [27] anticancer [28] and antihypertensive [29] properties. In addition, previous work found that aniline‐containing compounds had a broader range of biological activities [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been carried out on 2 H ‐1,4‐benzoxazin‐3(4 H )‐one in the medical field, while related pesticides have exhibited antifungal, [10,11] antibacterial, [12–14] herbicidal, [15,16] anticancer, [17,18] antitumor, [19] antileukaemia, [20] antagonist, [21] antioxidant, [22] and platelet aggregation inhibitor activities [23] ( Figure 1). Moreover, many reports demonstrate that compounds containing propanolamine moiety have wide‐ranging biological activities, including antifungal, [24] antibacterial, [25,26] anti‐HIV, [27] anticancer [28] and antihypertensive [29] properties. In addition, previous work found that aniline‐containing compounds had a broader range of biological activities [30] .…”
Section: Introductionmentioning
confidence: 99%